THE PHYSICS OF NANOTHERANOSTICS: HOW MOLECULES CONTROL DIABETES - Zoyirov Jahongir Nargiz o'g'li (Web of Journals Publishing, 2026)
This article analyzes the prospects of nanotheranostics in the management and monitoring of diabetes mellitus. It explores the concept of "smart" nanosystems that integrate high-sensitivity diagnostics and targeted therapy within a single platform. Special attention is paid to the physicochemical mechanisms of "closed-loop" systems. The paper describes the principles of optical glucose detection based on Fluorescence Resonance Energy Transfer (FRET) and the photoacoustic effect, which ensure non-invasive monitoring. The thermodynamic mechanism of insulin release from pH-responsive polymeric nanocapsules is analyzed in detail, focusing on how changes in electrostatic interaction and osmotic pressure—triggered by blood sugar fluctuations—regulate drug delivery. The author emphasizes the role of nanotechnology in overcoming biological barriers for oral peptide delivery and accelerating tissue regeneration in diabetic complications. The article concludes that the integration of biophotonics and nanoengineering is a key factor in the transition toward personalized diabetes, minimizing the risk of hypoglycemia and improving patient quality of life.
Keywords: nanotheranostics, diabetes mellitus,